2021
DOI: 10.1039/d0ew00787k
|View full text |Cite
|
Sign up to set email alerts
|

Simple preparation method for Styrofoam–TiO2 composites and their photocatalytic application for dye oxidation and Cr(vi) reduction in industrial wastewater

Abstract: This study investigates a simple method for the preparation of floating photocatalysts in which the surface of expanded polystyrene (EPS) is partially dissolved using a diluted solvent that contains TiO2 particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In fact, an increasing number of optimization and renovation for MPW photocatalytic treatment has been undertaken. 73,74 As is well known, reliable photocatalytic materials can significantly improve the efficiency of photodegradation. Previous studies mainly employed TiO 2 photocatalysts, which can degrade some refractory organic pollutants by producing free radicals (˙OH, ˙O2…”
Section: Emerging Treatment Technologiesmentioning
confidence: 99%
“…In fact, an increasing number of optimization and renovation for MPW photocatalytic treatment has been undertaken. 73,74 As is well known, reliable photocatalytic materials can significantly improve the efficiency of photodegradation. Previous studies mainly employed TiO 2 photocatalysts, which can degrade some refractory organic pollutants by producing free radicals (˙OH, ˙O2…”
Section: Emerging Treatment Technologiesmentioning
confidence: 99%
“…[17][18][19] Some typical inorganic photocatalysts with multifunctional characteristics have been reported by scientific researchers, such as TiO 2 , α-Fe 2 O 3 , In 2 S 3 , and ZnO. [20][21][22][23][24] However, there are some shortcomings, such as the electronhole pair recombination rate, fast agglomeration speed, and low solar energy utilization, which limit the efficiency of the above catalysts for Cr(VI) removal. [25][26][27] Therefore, the development of efficient photocatalysts to adsorb and convert Cr(VI) into a less toxic product Cr(III) is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Several substrates including synthetic polymers [29][30][31][32], polymer composites [33][34][35][36][37], wood [38], ceramics and silica [39,40], natural light-weight stones [41][42][43], and concrete [44] have been used to support photocatalysts. Testing in a laboratory revealed that FPWT efectively removes a variety of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%